2012
DOI: 10.1186/2162-3619-1-23
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of airflow alteration in central airways following tracheobronchial stent placement

Abstract: The computational fluid dynamics method, which provides an estimation of the pressure drop in the airway before and after the stent implantation, is proposed in this study. This method is based on the finite volume model. The pressure field was solved by the Navier-Stokes equations. The proposed methodology was evaluated in seven health people (control group) and in fourteen patients who were assigned in two groups, in which one was tracheal stenosis and the other was bronchial stenosis. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Secondly, the image-based model is generated from modern imaging techniques (CT and MRI) and represents the patient-specific airway configuration. The importance of realistic models has been emphasized in many studies because they provide the potential of conducting precise and personalized diagnosis, treatment, and prognostic of lung disease [ 11 , 16 , 19 ]. Thirdly, it is noted that image-based model is still unrealistic due to the anatomical complexity of airway (23 generations) and limited resolution of CT/MRI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the image-based model is generated from modern imaging techniques (CT and MRI) and represents the patient-specific airway configuration. The importance of realistic models has been emphasized in many studies because they provide the potential of conducting precise and personalized diagnosis, treatment, and prognostic of lung disease [ 11 , 16 , 19 ]. Thirdly, it is noted that image-based model is still unrealistic due to the anatomical complexity of airway (23 generations) and limited resolution of CT/MRI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the abnormal models, the airflow simulation works in a model with severe stenosis in the right main bronchus [ 12 ], a model with COPD [ 15 ], six models with mild or moderate asthma [ 11 ], and four models with left pulmonary artery sling [ 16 , 17 ] have been reported. Moreover, some studies have been done to evaluate the treatment responses, such as acute bronchodilation in asthmatics [ 18 ], tracheobronchial stent placement [ 19 ], and vascular ring surgery [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, CFD has been used to describe airflow in upper airway reconstructive surgery, as well as for modeling fluid flow through blood vessels . Previous work has shown that CFD has the potential for use in evaluating treatment planning for airway interventions . CFD allows for advanced diagnostic capabilities and is especially useful in cases involving multilevel or complex pathology.…”
Section: Discussionmentioning
confidence: 99%
“…4,[22][23][24] Previous work has shown that CFD has the potential for use in evaluating treatment planning for airway interventions. 4,[25][26][27] CFD allows for advanced diagnostic capabilities and is especially useful in cases involving multilevel or complex pathology. For example, if a patient has respiratory tract pathology at the level of the trachea, bronchi, and lungs, CFD allows for description the pathophysiology from each component in isolation or as a combined system.…”
Section: Discussionmentioning
confidence: 99%
“…The inlet boundary used constant velocity condition and flat velocity profile. The outlet boundary employed constant pressure condition and assigned to the zero pressure [21][22][23][24]. The boundary condition of the tracheal airway interior wall was applied with a no-slip condition.…”
Section: Momentum Equationmentioning
confidence: 99%